2022
DOI: 10.3390/cells11040723
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids Reduce Extracellular Vesicle Release from HIV-1 Infected Myeloid Cells and Inhibit Viral Transcription

Abstract: Of the 37.9 million individuals infected with human immunodeficiency virus type 1 (HIV-1), approximately 50% exhibit HIV-associated neurocognitive disorders (HAND). We and others previously showed that HIV-1 viral RNAs, such as trans-activating response (TAR) RNA, are incorporated into extracellular vesicles (EVs) and elicit an inflammatory response in recipient naïve cells. Cannabidiol (CBD) and Δ9-tetrahydrocannabinol (THC), the primary cannabinoids present in cannabis, are effective in reducing inflammation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 121 publications
1
14
0
Order By: Relevance
“…Interestingly, the same study reported significant reductions in HIV RNA and gag HIV protein in long-term infected cells treated with CBD 17 . In addition, DeMarino et al, reported the induction of a protective effect by reducing the release of extracellular vesicles from HIV-1 Infected monocytes and viral RNA 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the same study reported significant reductions in HIV RNA and gag HIV protein in long-term infected cells treated with CBD 17 . In addition, DeMarino et al, reported the induction of a protective effect by reducing the release of extracellular vesicles from HIV-1 Infected monocytes and viral RNA 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Ito et al [ 77 ] found that integrin αLβ2 and FGF2 mediate the emergence of tumor-associated macrophages from surrounding phagocytes, which were induced by the specific EV subtype (phosphatidylserine-exposing exosomes). Human immunodeficiency virus (HIV) infection leads to acquired immunodeficiency syndrome and other disorders [ 78 ]; Falasca et al [ 79 ] compared the protein contents of EVs derived from endothelial cells, leukocytes, and platelets from HIV patients with healthy volunteers and suggested EVs upregulated chronic inflammation to facilitate viral replication after HIV infection through γIFN, IL1α, NF-κB, and JAK/STAT3 signaling pathways. At present, COVID-19 still influences the world as a pandemic infectious disease; Pesce et al [ 80 ] isolated EVs from the plasma of mild and severe COVID-19 patients followed up by proteomics with healthy donors as the control group and observed both mild and severe case-derived EVs to be involved in the upregulation of the immune response for SARS-CoV-2, but differences in the immunomodulatory effects in the activation of immune cells (CD4 + T-cell) and acute inflammation, respectively, associated with different protein signatures in EVs.…”
Section: An Overview Of the Ev Biology In Disease Contextmentioning
confidence: 99%
“…These THC-mediated events are at least partly CB2-related and protective against SIV-enhanced periodontal disease. DeMarino et al have reported that CBD reduces extracellular vesicle release from HIV-infected monocytic cells and their viral cargo [ 66 ]. Otherwise, recent studies of the anti-viral properties of CIMPs are limited in number and are SARS-CoV-2 centric, as summarized in Table 5 .…”
Section: The Antimicrobial Properties Of Cannabis and Cannabis-derive...mentioning
confidence: 99%